Strengthening librarian professionalism through student internships at the Library of SMP Negeri 1 Cimahi - Hasna Nurul Fajri; Rashel Dika Azzahra; Tiara Putri Utami (Universitas Pendidikan Indonesia, 2025)
To carry out the tri dharma of higher education, students of the Library and Information Science study program at the Indonesian Education University are directed to be involved in the Non-Educational Professional Strengthening Program (P3NK), which is carried out in schools and institutional libraries. This research and community service were conducted at the SMP Negeri 1 Cimahi Library using the action research method, in which the author was directly involved in carrying out community service in the form of arranging and implementing operations in the school library for 40 working days. The practices carried out include aspects of collection development, organizing information, library services, preservation of library materials, application of information and communication technology (ICT) in the library, and being involved in other school programs integrated with the curriculum, namely the Pancasila Student Profile Strengthening Project (P5). The practices showed that several aspects still need improvement to comply with the National Standards for Junior High School Libraries. For this reason, special attention is required from the school and policymakers in the library to optimize the condition of the library in the future. Abstrak Dalam upaya menjalankan tri dharma perguruan tinggi, mahasiswa program studi Perpustakaan dan Sains Informasi Universitas Pendidikan Indonesia diarahkan untuk terlibat dalam kegiatan Program Penguatan Profesional Non-Kependidikan (P3NK) yang dilaksanakan di sekolah maupun di perpustakaan lembaga. Penelitian sekaligus pengabdian ini dilakukan di Perpustakaan SMP Negeri 1 Cimahi dengan metode action research, yang mana penulis terlibat langsung dalam mengerjakan pengabdian berupa penataan dan pelaksanaan operasional di perpustakaan sekolah selama 40 hari kerja. Praktik yang dilakukan meliputi aspek pengembangan koleksi, pengorganisasian informasi, layanan perpustakaan, preservasi bahan pustaka, penerapan teknologi informasi dan komunikasi (TIK) di perpustakaan, serta terlibat dalam program sekolah lainnya yang terintegrasi dengan kurikulum, yaitu Proyek Penguatan Profil Pelajar Pancasila (P5). Praktik yang dilakukan menunjukkan hasil bahwa dari beberapa aspek tersebut masih perlu peningkatan agar sesuai dengan Standar Nasional Perpustakaan Sekolah Menengah Pertama. Untuk itu, diperlukan perhatian khusus terhadap perpustakaan dari pihak sekolah maupun pemangku kebijakan agar dapat mengoptimalkan kondisi perpustakaan ke depannya. Kata Kunci: perpustakaan sekolah; profesi kepustakawanan; program magang